2014
DOI: 10.5194/acp-14-301-2014
|View full text |Cite
|
Sign up to set email alerts
|

Airborne measurements of gas and particle pollutants during CAREBeijing-2008

Abstract: Abstract. Measurements of gaseous pollutants -including ozone (O 3 ), sulfur dioxide (SO 2 ), nitrogen oxides (NO X = NO + NO 2 ), carbon monoxide (CO), particle number concentrations (5.6-560 nm and 0.47-30 µm) -and meteorological parameters (T , RH, P ) were conducted during the Campaigns of Air Quality Research in Beijing and Surrounding Regions in 2008 (CAREBeijing-2008), from 27 August through 13 October 2008. The data from a total 18 flights (70 h flight time) from near the surface to 2100 m altitude we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Three flight routes covering the area 38-40 • N and 114-118 • E from Tianjin to Shijiazhuang were flown repeatedly. Zhang et al (2014) showed that the flights sampling polluted air masses originated from urban areas south of the flight locations and suggested a limited influence from emission mitigation measures applied in the Beijing municipality at this time. Observed ozone precursors are elevated up to about 1.5 km, showing that the entire boundary layer was influenced by pollution.…”
Section: Trace Gas Vertical Distributionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three flight routes covering the area 38-40 • N and 114-118 • E from Tianjin to Shijiazhuang were flown repeatedly. Zhang et al (2014) showed that the flights sampling polluted air masses originated from urban areas south of the flight locations and suggested a limited influence from emission mitigation measures applied in the Beijing municipality at this time. Observed ozone precursors are elevated up to about 1.5 km, showing that the entire boundary layer was influenced by pollution.…”
Section: Trace Gas Vertical Distributionsmentioning
confidence: 99%
“…Flights followed linear routes at altitudes in the range 500-2100 m in order to sample both the boundary layer and the free troposphere. The instrumentation on board the aircraft is described by Zhang et al (2014) and includes ozone, CO, SO 2 and NO x samplers. The flight tracks are shown in blue in Fig.…”
Section: Airborne Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the concentration of specific components, such as SO 2 , CO, O 3 , NO x , etc. directly measured from the aircraft, facilitates quantitative analysis (e.g., Hatakeyama et al, 2004;Corrigan et al, 2008;Wang et al, 2008;Chen et al, 2013;Zhang et al, 2014). Airborne measurements allow to distinguish the FT air pollutants from those in the PBL, and in turn allow to identify the meteorological conditions related with the occurrence of high-concentration events in the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…A number of mobile laboratory measurements (Johansson et al, 2008;Li et al, 2009;Wang et al, 2009Wang et al, , 2011 and aircraft measurements (Huang et al, 2010;Zhang et al, 2011Zhang et al, , 2009Zhang et al, , 2014 have been used to determine pollution distributions, mainly within the megacity of Beijing. There have been several reports of model and satellite studies on the air pollution distribution in the NCP, or even the whole of China (Wei et al, 2011;Zhao et al, 2013;Ying et al, 2014;Ding et al, 2015Ding et al, , 2009).…”
Section: Introductionmentioning
confidence: 99%